Penyusunan Perencanaan Perangkat Pembelajaran Bahasa Arab - Enramika, Tomi (Medan Resource Center, 2022)
This study aims to develop an effective and efficient Arabic language learning plan to improve the quality of the teaching and learning process. This research uses a qualitative approach with descriptive methods. Data were collected through observations, in-depth interviews, and document analysis of existing learning plans. The focus of the research is to identify the main components of Arabic language learning tools, including learning objectives, teaching materials, teaching methods, learning media, as well as evaluation and assessment. The results of the study indicate that a good Arabic language learning plan should include clear and specific learning objectives, teaching materials that are appropriate to the students' proficiency levels, varied and interactive teaching methods, supportive learning media, and a comprehensive and continuous evaluation system. These findings are expected to provide practical guidelines for educators in designing more effective Arabic language learning tools, thereby enhancing students' motivation and learning outcomes. This study also provides recommendations for further development in the implementation of Arabic language learning tools at various educational levels.